Determination of simazine in fish and shrimp samples using ultra performance liquid chromatography tandem mass spectrometer (uplc-ms/ms) / Amirul Ashraf Bin Jamaluddin - Amirul Ashraf, Jamaluddin (2014)
Ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method was successfully developed and validated for the analysis of simazine in fish and shrimp samples at trace levels to meet European Union requirements and import requirements from certain countries. This method also utilized a simple, fast and inexpensive extraction technique called QuECheRS (quick, easy, cheap, rugged and safe). Matrix-matched calibration standard are used to construct a calibration curve and Ethoprophos is used as internal standard. At optimal conditions, the chromatographic separation was achieved in less than 10 minutes with the total run time of 13.5 minutes. The mean recoveries for fish matrix ranged from 101 % to 107 % while shrimp matrix shows the range from 97 % to 101 %. Limit of detection (LOD) for simazine in fish and shrimp were 1.18 ng/g and 1.06 ng/g respectively. The limits of quantification (LOQ) were reported as 3.52 ng/g in fish matrix and 3.19 ng/g in shrimp matrix. Results from this study showed that the concentration of simazine obtained in fish and shrimp samples were below the limit of quantification and it is reported as not detected in the sample.